A Possession Forever A Guide to Using Commemorative Memorials and Monuments in the Classroom - Kerby , Martin; Baguley , Margaret; Gehrmann , Richard; Bedford , Alison (Open textbook library., 2021)
This open textbook will guide educators and students through the process of using local monuments and memorials to contextualise, interrogate and extend their knowledge of historical events at a national and international level. Students will learn how to use local history to create an organic patchwork of local stories, interviews, photographs and artefacts contributed by, and for, the community and contextualised nationally and internationally. Through this process they will assume the role of historians rather than passive consumers of dominant ideologies and understand how historical events have shaped diverse views, including their own, of issues such as social justice, democracy, human rights and citizenship.